1988
DOI: 10.1021/bi00403a024
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of 15-hydroxyeicosatetraenoic acid to 11-hydroxyhexadecatrienoic acid by endothelial cells

Abstract: Cultured endothelial cells take up 15-hydroxyeicosatetraenoic acid (15-HETE), a lipoxygenase product formed from arachidonic acid, and incorporate it into cellular phospholipids and glycerides. Uptake can occur from either the apical or basolateral surface. A substantial amount of the 15-HETE incorporated into phospholipids is present in the inositol phosphoglycerides. 15-HETE is converted into several metabolic products that accumulate in teh extracellular fluid; this conversion does not require stimulation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 39 publications
3
23
0
Order By: Relevance
“…Based on this, we conclude that ␤-oxidation is an alternative pathway for EET metabolism that occurs when conversion to DHET is limited. Peroxisomal ␤-oxidation is the main metabolic pathway in endothelial cells for other types of fatty acid biomediators, including 15-and 12-hydroxyeicosatetraenoic acid (HETE) and 13-hydroxyoctadecadienoic acid (41)(42)(43). However, the present results indicate that this is not the primary pathway for EET metabolism in the coronary endothelium, since appreciable amounts of EET are channeled into the ␤-oxidation pathway only when DHET formation is inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this, we conclude that ␤-oxidation is an alternative pathway for EET metabolism that occurs when conversion to DHET is limited. Peroxisomal ␤-oxidation is the main metabolic pathway in endothelial cells for other types of fatty acid biomediators, including 15-and 12-hydroxyeicosatetraenoic acid (HETE) and 13-hydroxyoctadecadienoic acid (41)(42)(43). However, the present results indicate that this is not the primary pathway for EET metabolism in the coronary endothelium, since appreciable amounts of EET are channeled into the ␤-oxidation pathway only when DHET formation is inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the specificity of defective oxidation in the Zellweger cells, [3H]-1 5-HETE was tested under identical conditions. Previous work has indicated that 1 5-HETE can be oxidized to a similar 16 carbon polar metabolite, 16:3(1 -OH) (12). When incubated with normal human skin fibroblasts, [3H]-1 5-HETE was converted to several more polar metabolites, including a major one which migrated at 31.2 min and comprised 34% ofthe total radioactivity detected (Fig.…”
Section: Introductionmentioning
confidence: 87%
“…12-HETE is preferentially incorporated into the choline and the ethanolamine phosphoglycerides (7), whereas a substantial fraction of 1 5-HETE is recovered in the inositol phosphoglycerides (12,13 (12). These 16-carbon metabolites are most likely produced through oxidative removal of 4 carbons from the carboxyl terminus of the HETE.…”
Section: Introductionmentioning
confidence: 99%
“…HUVECs were obtained by collagenase digestion as previously described, 23 and the types of cells were verified by morphology and the presence of factor VIII antigen. Cells were grown to confluence in medium 199 supplemented with 10% heat-inactivated FBS, 30 g/mL EC growth supplements (Sigma), 100 g/mL heparin, 0.1 mmol/L nonessential amino acids, 200 U/mL penicillin, and 200 g/mL streptomycin in a humidified incubator with 95% air/5% CO 2 at 37°C.…”
Section: Cell Culture and Experimental Stimulationmentioning
confidence: 99%